Comparison of third generation long Gamma nail and femur intramedullary nail for the treatment of femoral subtrochanteric fractures - Çepni, Şahin; Veizi, Enejd; Şahin, Ali; Fırat, Ahmet; Subaşı, Özay; Polat, Yağmur (Journal of Surgery and Medicine, 2021)
Background/Aim: Internal fixation is the current gold standard procedure in treatment of subtrochanteric femur fractures. One of the most common causes of morbidity after subtrochanteric femoral fracture treatment is mechanical complications, such as implant failure. The aim of this study is to share our experience and compare the radiological and functional results of two different fixation implants in patients with subtrochanteric fractures. Methods: A cohort of 57 patients with a subtrochanteric fracture operated using a third generation Gamma nail (G3LN) or an anterograde intramedullary nail (AIMN) were prospectively followed up. Twenty-eight underwent fracture fixation with the Gamma nail while the other twenty-nine were operated using a conventional AIMN. All patients were followed up until union or, in case of a revision, healing and recovery. Their radiological findings were retrospectively analyzed, and the functional results were assessed using a Harris Hip Score. Results: Data regarding demographic properties such as sex, trauma mechanism and smoking were similar for the subgroups (P<0.05 for each). Blood loss amount, surgery time, hospital stay and follow up time were also similar between the two groups (P>0.05 for each). Compared to the AIMN group, whose reduction was mostly acceptable (48.28%), the majority of G3LN patients (57.14%) had an anatomical reduction on early follow up. Most fractures, regardless of the implant used, needed an open reduction. Both implants showed similar union time and had similar final HHS scores. None of the complication rates reached statistical significance between the two groups (P>0.05 for each). Conclusion: Both third-generation Gamma Nail implant and anterograde intramedullary nailing are viable means of fixation for subtrochanteric hip fractures. They lead to similar and few complications while providing a rigid and secure fixation. These findings lead us to believe that good reduction and adherence to the principles of internal fixation rather than implants used are the key to success in the treatment of subtrochanteric fractures.